Manajemen Sumber Daya Manusia sebagai Kunci Peningkatan Mutu Pendidikan di Sekolah Menengah Pertama (SMP) - Dani, Elly Chusmala; Rindaningsih, Ida (Lembaga Yasin AlSys, 2025)
Human resource management (HRM) is one of the key elements in improving the quality of education, particularly at the junior high school (SMP) level. HRM in education encompasses a series of activities aimed at managing and developing human resources within educational environments, including teachers, administrative staff, and educational personnel. The purpose of this article is to analyze the role of HRM in enhancing the quality of education in SMPs through an integrated approach, involving planning, development, and performance evaluation of teachers and educational staff. Teachers, as the primary human resources, play a central role in the learning process. Effective HR management enables schools to create a conducive learning environment, improve teacher professionalism, and enhance student achievement. The objective of this study is to identify effective human resource management strategies to support the achievement of educational goals. Additionally, the study is expected to contribute to the development of HRM in education, particularly in efforts to improve the quality of education in junior high schools. The research method used in this study is a literature review. The steps include selecting sources, determining inclusion and exclusion criteria (limiting the time frame), collecting data, and analyzing the data. The findings indicate that the implementation of appropriate HR management strategies can improve the quality of learning, students' academic outcomes, and the overall school environment, thereby enhancing the quality of education.